Morphology Detection in Archaeological Ancient Sites by Using UAVs/Drones Data and GIS techniques - Qubaa , Abdalrahman R.; Hamdon, Alaa N.; Al Jawwadi, Taha A. (Iraqi Journal of Science, 2021)
Today, Unmanned Aerial Vehicles (UAVs) or Drones are a valuable source of data on inspection, surveillance, mapping and 3D modelling matters. Drones can be considered as the new alternative of classic manned aerial photography due to their low cost and high spatial resolution. In this study, drones were used to study archaeological sites. The archaeological Nineveh site, which is a very famous site located in heart of the city of Mosul, in northern Iraq, was chosen. This site was the largest capital of the Assyrian Empire 3000 years ago. The site contains an external wall that includes many gates, most of which were destroyed when Daesh occupied the city in 2014. The local population of the city of Mosul has also largely overtaken the central part of this archaeological site, while the northern and southern parts are still uninhabited. The awareness of the existence of unchanged surface and ground forms in the northern or southern parts led us to prepare an urgent study to interpret the outer surface of those parts and to analyze any discovery in the surface morphology. So, drone data and GIS technologies were used in this study to find any discovery that could aid in understanding the original surface of this ancient site. Visual and digital interpretations of satellite images, drone images, and Digital Surface Models (DSMs) were used to analyze and study the data. As a final result, certain morphological features were identified in the southern parts of the ancient site which could be a new archaeological and compositional discovery with reference to the earlier activities of the ancient society during the Assyrian empires, represented by the ditches and building lands used by the ancient inhabitants. Small modern tunnels penetrated the ancient wall were also discovered in addition, to a drainage canal and a motorway newly constructed during the occupation of the city that had penetrated the archaeological land.